Information transmission and ownership consolidation in aid programs - Dreher, Axel; Langlotz, Sarah; Marchesi, Silvia (Economic inquiry, 2017)
We investigate the degree of leeway donors of foreign aid should grant to recipient governments when their preferences over how to implement the aid are different, and both the donor and recipient possess some private information about the most effective policies. Intuitively, our model shows that donors should stay in control of how their aid is spent when their own private information is more important than the private information of the recipient. Less obviously, an increase in the difference of preferences between donors and recipients can increase rather than decrease the leeway that donors should grant the recipients, as the recipients' information gains in importance relative to those of the donors, and recipients become less likely to communicate truthfully. We test the model using dyadic data for 28 bilateral aid donors and 112 recipients, over the 1995-2010 period. Our proxy for “centralized” aid is project aid, while budget aid leaves more leeway to the recipient and thus proxies for “decentralized” aid. In line with the model, misaligned interests and informational asymmetries indeed influence the shares of aid given as budget and project aid. (JEL C23, D82, F33,O1)